Molecular dynamics simulation of nanoparticle effect on melting enthalpy of paraffin phase change material. (April 2020) - Zhao, C.Y.; Tao, Y.B.; Yu, Y.S.
Highlights: Significant melting enthalpy reduction was found in NPCMs. Interaction between nanoparticles and PCM contributes to the reduction. A parameter was defined to evaluate the effect of the interaction. Dense phase is the internal reason for NPCM melting enthalpy reduction. Abstract: In order to enhance the thermal conductivity of phase change material (PCM), many studies on preparation of composite PCM with nanoparticles (NPCM) have been performed. However, most of the studies only focused on PCM thermal conductivity enhancement, and ignored the melting enthalpy reduction caused by nanoparticles. In present paper, molecular dynamics (MD) method was adopted to study the effect of nanoparticles (CuO) on PCM (paraffin) melting enthalpy and to reveal the mechanism of PCM melting enthalpy reduction. The results showed that the melting enthalpy quickly decreased with the increase of nanoparticle mass fractions. For the NPCM with 19.72 wt.% nanoparticles, the melting enthalpy decreased by about 51.5%. The interactions between nanoparticles and PCM also contribute to melting enthalpy reduction except the nanoparticle mass fraction. Then, a parameter ( F c) was defined to reveal the effect of the interactions on NPCM melting enthalpy. With the nanoparticle mass fraction increasing, the interaction was strengthened and the value of F c was quickly decreased, especially when the nanoparticle mass fraction was lower than 10 wt.%. The dense phase of paraffin was found around nanoparticles. The existence of dense phase caused by the interaction between nanoparticles and PCM is the internal reason for NPCM melting enthalpy reduction.